STUDENTS’ PERCEPTION TOWARD TEACHERS’ ATTITUDE, TEACHING STYLE, AND TEACHING STRATEGIES IN LEARNING ENGLISH - Ferdiyanto, Feri; Hamdani, Beny; Islam, Raudhatul; Harzanah, Novi Dwi (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
Teachers’ attitudes, teaching styles, and teaching strategies are needed to motivate students’ enthusiasm and interest in learning English. This study aims to analyze students’ perceptions of teachers’ attitudes, styles, and strategies. This study uses quantitative method with a survey design which used a questionnaire as the research instrument to get data. The study is conducted by using Google Form to get the data from the participants. The population of this study is the students of English Department of Zainul Hasan Islamic University Genggong. The sample used in this study are thirty-six students that are from several high schools around the area of Kraksaan. The collected data of this study is then analyzed by using a statistical formula to get the percentage of each question. The results shows that most of the teachers high schools around the area of Kraksaan have good attitudes and strategies in teaching English.